Distribution and abundance of Ateles belzebuth E. Geoffroy and Ateles chamek Humboldt (Cebidae: Primates) in the Pacaya Samiria National Reserve, Peru - Aquino, Rolando (2006)
The study deals with the habitat, inter-especific associations, group size and population density of two Ateles species that inhabit the Pacaya Samiria National Reserve. Data were collected during inventories and transect censuses between january 1997 and february 1999, september — october 2000, august –- september 2002 and January 2003. On the left bank of the Río Samiria, Ateles balzebuth E. Geffroy and Ateles chamek Humboldt share the habitat forming mixed groups. Average group size for A. belzebuth was 5,1 individuals/group and for A. chamek 7,3 individuals/group. Estimated population density for A. belzebuth was 1,02 individuals/km2 and for A. chamek 0,51 individuals/km2 . We discuss and analyze the factors that may have influenced the drastic reduction of both populations.